The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2139/ssrn.2475518
|View full text |Cite
|
Sign up to set email alerts
|

The Propagation of Shocks Across International Equity Markets: A Microstructure Perspective

Abstract: We study the high-frequency propagation of shocks across international equity markets. We identify intraday shocks to stock prices, liquidity, and trading activity for 12 equity markets around the world based on non-parametric jump statistics at the 5-minute frequency from 1996 to 2011. Shocks to prices are prevalent and large, with regular spillovers across markets -even within the same 5-minute interval. We find that price shocks are predominantly driven by information rather than liquidity. Consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…Brenner et al (2009), who study responses of U.S. stock, Treasury, and bond markets to U.S. macroeconomic surprises, also find fundamentals-driven interrelations on a daily basis. This finding is in line with Bongaerts et al (2014) and Füss et al (2017), who document that jumps and co-jumps in prices are often found in relation to U.S. macroeconomic announcements.…”
Section: Related Literaturesupporting
confidence: 89%
“…Brenner et al (2009), who study responses of U.S. stock, Treasury, and bond markets to U.S. macroeconomic surprises, also find fundamentals-driven interrelations on a daily basis. This finding is in line with Bongaerts et al (2014) and Füss et al (2017), who document that jumps and co-jumps in prices are often found in relation to U.S. macroeconomic announcements.…”
Section: Related Literaturesupporting
confidence: 89%
“…In fact most of the research concentrates either on the equity market or on bond liquidity at daily or weekly frequency. A recent study by Bongaerts et al (2015) directly identifies liquidity shocks in different equity markets at five-minute resolution and does not find any evidence for spillovers in time nor across markets, challenging the concepts of liquidity dry-ups and contagion of liquidity shocks.…”
Section: Introductionmentioning
confidence: 93%
“…Common to these detection methods is that they are effectively carried out on discrete time intervals, even when highfrequency data are available. For example Chavez-Demoulin and McGill (2012) samples stock-returns over 15-min periods, Bongaerts et al (2015) over 5 minutes or Bormetti et al (2015) at 1-minute frequency. However the discrete time grid might miss events that occur at shorter time-scales and, when modelled as Hawkes processes, forces discrete time on the originally continuous Hawkes process.…”
Section: Event Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The critical value is based on the 99th-percentile of a Gumbel distribution. We follow previous empirical papers on jump identification and choose a return frequency of five minutes to avoid most market microstructure noise (e.g., Evans (2011); Jiang, Lo, and Verdelhan (2011); Bongaerts, Roll, Rösch, Van Dijk, and Yuferova (2014)). This ensures that effects such as highfrequency trading, short-term anomalies, or bid-ask bounces will not contaminate our results.…”
Section: Jump Identificationmentioning
confidence: 99%